1987
DOI: 10.1037/0022-0663.79.3.249
|View full text |Cite
|
Sign up to set email alerts
|

The positive effects of writing practice on integration of foreign words in memory.

Abstract: The effect of copying foreign language vocabulary words and/or pronouncing them aloud while attempting to learn their English counterparts was investigated. In Experiment 1, writing practice enhanced written recall of the foreign words in response to their English equivalents. Recall of the foreign words in the oral modality was not influenced by these variables. In Experiment 2, when recall of English words was measured, neither variable was found to have a significant effect. In Experiment 3, written free re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 8 publications
4
37
3
Order By: Relevance
“…The combined findings of Thomas and Dieter (1987) and the present study also suggest that the effects of word writing may depend upon experimental paradigm and methodology. Whereas Thomas and Dieter found positive effects for word writing on some measures and null effects on others, the present study revealed negative effects for word writing using LPSP-written scoring.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The combined findings of Thomas and Dieter (1987) and the present study also suggest that the effects of word writing may depend upon experimental paradigm and methodology. Whereas Thomas and Dieter found positive effects for word writing on some measures and null effects on others, the present study revealed negative effects for word writing using LPSP-written scoring.…”
Section: Discussionmentioning
confidence: 63%
“…Three potentially critical differences between the present study and Thomas and Dieter's (1987) study concern task difficulty, presentation format, and scoring. First, more target words were used in Thomas and Dieter's study, but the inclusion of an additional repetition for each word and an additional 4 seconds for every repetition may have resulted in a less demanding vocabulary learning task than that of the present study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, such a verification stage can contribute to retention in combination with the act of writing down the inferred and verified meaning (Schouten-van Parreren; cf. Thomas & Dieter, 1987). An additional point of interest concerning the meaning-inferred method is the amount of time the procedure takes.…”
mentioning
confidence: 99%
“…However, previous research has offered mixed perceptions about the effect of copying vocabulary exercises. Thomas and Dieter (1987) stated that copying practice was beneficial for the accuracy and completeness of writing a word. Hummel (2010) confirmed the merits of rote-copying for learning L2 words that copying exercises promoted vocabulary recall in terms of immediate memory.…”
Section: Vocabulary Exercisesmentioning
confidence: 99%